The Eagle Ford Shale
DOI: 10.1306/13541961m1103589
|View full text |Cite
|
Sign up to set email alerts
|

An SEM Study of Porosity in the Eagle Ford Shale of Texas—Pore Types and Porosity Distribution in a Depositional and Sequence-stratigraphic Context

Abstract: Although typically considered with a focus on high-resolution petrography, shale porosity should not be thought of as a stand-alone petrographic feature. Shale and mudstone porosity is the outcome of a long succession of processes and events that span the continuum from deposition through burial, compaction, and late diagenesis. For the Eagle Ford Shale this journey began with accumulation in intra-shelf basins at relatively low latitudes on a southeast-facing margin during early parts of the late Cretaceous. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
18
0

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 26 publications
2
18
0
Order By: Relevance
“…They show that the sample is comprised of 67% calcite, 8.7% quartz, 6.2% Illite and Mica, 4.2% Illite/Smectite mixture, 5% K-feldspar, 4.1% plagioclase, and minor amounts of pyrite, kaolinite, chlorite, apatite, and siderite. This composition is similar to that measured by others[6][7][8], except for the lack of small amounts of gypsum and dolomite.The cation exchange capacity of the Eagle Ford shale is 89.1 meq/kg. The Ca and alkalinity (HCO3 -) released into brine by Eagle Ford shale upon exposure to 0.5 M MgCl2 after rinsing three times in brine were also measured.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…They show that the sample is comprised of 67% calcite, 8.7% quartz, 6.2% Illite and Mica, 4.2% Illite/Smectite mixture, 5% K-feldspar, 4.1% plagioclase, and minor amounts of pyrite, kaolinite, chlorite, apatite, and siderite. This composition is similar to that measured by others[6][7][8], except for the lack of small amounts of gypsum and dolomite.The cation exchange capacity of the Eagle Ford shale is 89.1 meq/kg. The Ca and alkalinity (HCO3 -) released into brine by Eagle Ford shale upon exposure to 0.5 M MgCl2 after rinsing three times in brine were also measured.…”
supporting
confidence: 89%
“…In the former they are rich sources of oil and natural gas, and in the latter they serve as cap rock to prevent carbon dioxide escape. Shales are complex assemblages of fine mineral fragments and organic matter of varying reactivity [5], and in many cases are dominated by highly reactive carbonate minerals (e.g., Eagle Ford shale > 60% calcite [6][7][8], Wolfcamp and Marcellus shales >80% calcite+dolomite). Shales are exposed to injected fluids during hydraulic fracturing and geological carbon sequestration leading to dissolution and secondary mineral precipitation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Key products of these reactions include bicarbonate ions, reduced manganese and iron, and sulphide, all of which can be incorporated into early diagenetic minerals such as calcite, pyrite, siderite and dolomite (Berner, 1984;Raiswell, 1988;Macaulay et al, 1993;Raiswell and Fisher, 2000;Taylor et al, 2000). Over the past decade, an increasing number of case studies have suggested that significant amounts of kaolinite in some ancient mudstone successions is of early diagenetic origin (Aplin and Macquaker, 2012;Macquaker et al, 2014;Taylor and Macquaker, 2014;Schieber et al, 2016), instead of being introduced to sedimentary basins by rivers that had intensely weathered soils in their catchment areas (Thiry, 2000;Junttila et al, 2005;Wendler et al, 2016). Over the past decade, an increasing number of case studies have suggested that significant amounts of kaolinite in some ancient mudstone successions is of early diagenetic origin (Aplin and Macquaker, 2012;Macquaker et al, 2014;Taylor and Macquaker, 2014;Schieber et al, 2016), instead of being introduced to sedimentary basins by rivers that had intensely weathered soils in their catchment areas (Thiry, 2000;Junttila et al, 2005;Wendler et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…That clay minerals can also form during this shallow burial stage has been known for some time (Odin, 1990;Mackenzie and Kump, 1995;Michalopoulos and Aller, 1995) but still is not considered of significant importance in many published studies of mudstones. Over the past decade, an increasing number of case studies have suggested that significant amounts of kaolinite in some ancient mudstone successions is of early diagenetic origin (Aplin and Macquaker, 2012;Macquaker et al, 2014;Taylor and Macquaker, 2014;Schieber et al, 2016), instead of being introduced to sedimentary basins by rivers that had intensely weathered soils in their catchment areas (Thiry, 2000;Junttila et al, 2005;Wendler et al, 2016).…”
Section: Introductionmentioning
confidence: 99%